Wound Closure Following Intervention for Closed Orthopedic Trauma. Issue 2 (February 2022) - Gotlin, Matthew J; Catalano, William; Levine, Jamie P.; Egol, Kenneth A.
Highlights: There are both patient and surgical factors that may predispose individuals to wound healing issues. Wounds that are in direct communication with bony fractures are at risk due to local tissue trauma, hematoma formation, and injured vasculature. There is no evidence of a difference in surgical site infection following closure with sutures or staples in orthopedic trauma surgery. Incisional negative pressure wound therapy cannot be recommended for routine use. We as surgeons can affect patient outcomes based on decisions we make at the time of wound closure. Abstract: The method of skin closure and post-operative wound management has always been important in orthopedic surgery and plays an even larger role now that surgical site infection (SSI) is a national healthcare metric for both surgeons and hospitals. Wound related issues remain some of the most feared complications following orthopedic trauma procedures and are associated with significant morbidity. In order to minimize the risk of surgical site complications, surgeons must be familiar with the physiology of wound healing as well as the patient and surgical factors affecting healing potential. The goal of all skin closure techniques is to promote rapid healing with acceptable cosmesis, all while minimizing risk of infection and dehiscence. Knowledge of the types of closure material, techniques of wound closure, surgical dressings, negative pressure wound therapy, and other local modalities is important to optimize wound healing. There is no consensus in the literature as to which closure method is superior but the available data can be used to make informed choices. Although often left to less experienced members of the surgical team, the process of wound closure and dressing the wound should not be an afterthought, and instead must be part of the surgical plan. Wounds that are in direct communication with bony fractures are particularly at risk due to local tissue trauma, resultant swelling, hematoma formation, and injured vasculature.